Determination of Total Selenium in Pharmaceutical and Herbal Supplements by Hydride Generation and Graphite Furnace Atomic Absorption Spectrometry. (27th November 2019) - Kazi, Tasneem G; Kolachi, Nida F; Afridi, Hassan I; Brahman, Kapil Dev; Shah, Faheem
Abstract: The total selenium (Se) was determined in herbal and pharmaceutical supplements used for liver diseases. The total Se contents were determined in different pharmaceutical and herbal supplements by hydride generation atomic absorption spectrometry (HGAAS) and graphite furnace atomic absorption spectrometry (GFAAS) after microwave-assisted acid digestion. The accuracy of the techniques was evaluated by using certified reference material and the standard addition method. The recoveries of total Se were 99.4 and 99.0% for HGAAS and GFAAS, respectively. The precision of the techniques expressed as RSD were 2.34 and 4.54% for HGAAS and GFAAS measurements, respectively. The LOD values for HGAAS and GFAAS were 0.025 and 0.052 μg/g, respectively. The concentrations of Se in pharmaceutical and herbal supplements were found in the range of 19.2–53.8 and 25.0–42.5 μg/g, respectively, corresponding to 35–76% and 45–76% of the total recommended dose of Se for adults.